2021
DOI: 10.1371/journal.pone.0253007
|View full text |Cite
|
Sign up to set email alerts
|

Screening for SARS-CoV-2 by RT-PCR: Saliva or nasopharyngeal swab? Rapid review and meta-analysis

Abstract: Background Diagnosis of COVID-19 in symptomatic patients and screening of populations for SARS-CoV-2 infection require access to straightforward, low-cost and high-throughput testing. The recommended nasopharyngeal swab tests are limited by the need of trained professionals and specific consumables and this procedure is poorly accepted as a screening method In contrast, saliva sampling can be self-administered. Methods In order to compare saliva and nasopharyngeal/oropharyngeal samples for the detection of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…In addition, direct RT-qPCR of heated saliva samples without an RNA extraction step can shorten the assay time, use less sample (volume), and thus alleviate reagents shortage making it suitable for general screening [ 15 , 16 , 17 , 18 , 19 , 20 ]. Recently, detection of SARS-CoV-2 was compared between saliva and NP or OP swab samples [ 14 ]. This meta-analysis conclusively demonstrated that saliva was as valid as NP sampling for the detection of SARS-CoV-2 infection in both symptomatic and asymptomatic carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, direct RT-qPCR of heated saliva samples without an RNA extraction step can shorten the assay time, use less sample (volume), and thus alleviate reagents shortage making it suitable for general screening [ 15 , 16 , 17 , 18 , 19 , 20 ]. Recently, detection of SARS-CoV-2 was compared between saliva and NP or OP swab samples [ 14 ]. This meta-analysis conclusively demonstrated that saliva was as valid as NP sampling for the detection of SARS-CoV-2 infection in both symptomatic and asymptomatic carriers.…”
Section: Discussionmentioning
confidence: 99%
“…It also provides comparable sensitivity to NP swabs [ 8 , 10 , 11 , 12 , 13 ]. Recently, the detection of SARS-CoV-2 was compared between saliva and NP or OP swab samples in a meta-analysis [ 14 ]. This conclusively demonstrated that the saliva was as valid as nasopharyngeal sampling for the detection of SARS-CoV-2 infection in both symptomatic and asymptomatic carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Mouth and nose swabs and saliva samples are used because (a) both procedures are less invasive than nasopharyngeal or oropharyngeal swabs and are therefore more suitable for very young children (mouth swaps are dipped into medical glucose solution), and (b) they are an easier and more reliable method for self-testing. The combination of mouth and nose swabs and saliva samples has been shown to be of similar quality to a deep nasopharyngeal swab (22)(23)(24)(25)(26). The initial swabs are taken by trained staff during the first home visit.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Along with the development of vaccines and treatments against virus, the diagnosis of viral infections using high-speed and accurate ribonucleic acid (RNA) detection assays is paramount, as various studies have reported ( Brown et al, 2021 ; Garg and Garg, 2021 ; Howe et al, 2021 ; Ibrahimi et al, 2021 ; Luethy and Johnson, 2021 ; Van Rijn and Boonstra, 2021 ; Yuan et al, 2021 ). For example, an integrated microfluidic system with reverse transcription-polymerase chain reaction (RT-PCR) has been developed for the rapid detection of influenza A viruses ( Shen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The essential steps of isolating RNA from a viral sample and synthesizing complementary DNA (cDNA) through an RT reaction, then amplifying this cDNA using PCR, are routinely conducted manually ( Garg and Garg, 2021 ; Voon et al, 2021 ; Yuan et al, 2021 ). In general, a total reaction time of at least 4 h is required to isolate viral RNA from biological samples, synthesize cDNA, and perform PCR according to the manufacturer protocols ( Arevalo-Rodriguez et al, 2020 ; Ibrahimi et al, 2021 ). Moreover, conventional RT-qPCR analyses rely on 96- or 384-well plates, limiting high-throughput sample analysis in the case of mass infection.…”
Section: Introductionmentioning
confidence: 99%